(untitled) (The Journal of Academic Development, 2023)
Increasing debt levels in Nepal have led to concerns about the impact on the country’s real GDP. This paper investigates the impact of both internal and external outstanding debt, along with gross fixed capital formation, broad money supply, total trade, and national consumer price index, on real GDP in Nepal from 1975 to 2021. The study used domestic data sets and ordinary least square series. Unit root and cointegration tests were conducted. The cointegration results confirmed a long-run relationship between the variables. The empirical results showed that both internal and external outstanding debt contributed to real GDP in Nepal. These results were supported by econometric diagnostic tests. Based on the results, the paper recommends that taking public debt and investing in the public sector can be beneficial for real sector output in Nepal. However, it is important to manage debt levels carefully to avoid negative consequences in the long run.